(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article we focus on the definitions of medical vocabulary and medical terminology. The concept of "medical terminology" implies terms of modern medical science, and the concept of "medical vocabulary" unites medical names that function not only in scientific, but also in other subsystems of language, that is, in synchrony and diachrony. Medical vocabulary combines specialized and non-specialized medical names that function in scientific and other subsystems of language. The main part of medical vocabulary is medical terminology.